The Influence of AI Literacy, AI Attitude, and Career Self-Efficacy on Job-Seeking Anxiety among Final-Year University Students - Adinda Zalfa Prayudya; Sandi Nasrudin Wibowo (Greenation Research & Yayasan Global Resarch National, 2026)
The study entitled “The Influence of Career Self-Efficacy on Job Seeking Anxiety: The Mediating Role of AI Attitude and AI Literacy among Final-Year University Students” examines final-year students as the research object to understand psychological and technological factors influencing anxiety during the job search process. This study aims to analyze the impact of Career Self-Efficacy on Job Seeking Anxiety and to evaluate the mediating roles of AI Literacy and AI Attitude. A quantitative approach with a causal associative design was employed, involving 120 respondents who completed a structured questionnaire, and the data were analyzed using SEM-PLS. The results show that Career Self-Efficacy has a significant negative effect on Job Seeking Anxiety, while AI Literacy and AI Attitude also directly reduce anxiety related to job searching. However, neither AI Literacy nor AI Attitude mediates the relationship between Career Self-Efficacy and Job Seeking Anxiety, and no chain mediation effect was found. The study concludes that confidence in career-related abilities is the primary factor that decreases job-seeking anxiety, whereas AI Literacy and AI Attitude serve as supportive factors that contribute directly without acting as mediators.